Report of the Working Group on Environmental and Occupational Health for the Tenth Five Year Plan - Planning Commission (Planning Commission, 2001)
The planning commission constituted a working group on environment and health to formulate policy guidelines, strategies and programme objectives during the tenth-five year plan period (2002-2007). As a part of the Working Group, a Sub-group on Environmental and Occupational Health consisting of fifteen Members (annexure 1) was set up with following "Terms of Reference".
Government of India Planning Commission
Government of India Planning Commission